2020
DOI: 10.18506/anemon.647705
|View full text |Cite
|
Sign up to set email alerts
|

Üstün Zekalı ve Yetenekli Öğrencilerin Bilim ve Sanat Merkezindeki ve Okuldaki Sosyal Bilgiler Dersine Yönelik Metaforik Algıları

Abstract: Sosyal bilgilerÖğrenci algısı Üstün zekalı ve yetenekli öğrenci ÖZ Bu araştırmanın amacı; ortaokula devam eden üstün zekalı ve yetenekli öğrencilerin bilim ve sanat merkezindeki sosyal bilgiler dersi ile okuldaki sosyal bilgiler dersine yönelik metaforik algılarını belirlemektir. Araştırma, olgu bilim olarak desenlenmiştir. Araştırma, 40 öğrenci ile yürütülmüştür. Araştırmada veri toplama aracı olarak metafor belirleme formu kullanılmıştır. Elde edilen veriler üzerinde içerik analizi yapılmıştır. Üstün zekalı … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
3
0
2
Order By: Relevance
“…It was determined the study that the support education program increased the motivation and attitude the gifted students in the social studies lesson, but the increase was only meaningfully reflected in the attitude. In Bolat's (2020) study, it is seen that gifted students have a positive perception towards the social studies lesson.…”
Section: Social Studies Lessonmentioning
confidence: 87%
See 1 more Smart Citation
“…It was determined the study that the support education program increased the motivation and attitude the gifted students in the social studies lesson, but the increase was only meaningfully reflected in the attitude. In Bolat's (2020) study, it is seen that gifted students have a positive perception towards the social studies lesson.…”
Section: Social Studies Lessonmentioning
confidence: 87%
“…In literature, there are studies examining views, motivations and attitudes of gifted students towards mathematics, science, social studies and Turkish lessons (Alevli & Okur, 2021;Asut & Köksal, 2015;Bolat, 2020;Gubbels, Segers & Verhoeven, 2014;Kahyaoglu & Pesen, 2013;Kanlı & Emir, 2009;Kunt & Tortop, 2017;Levenberg & Shaham, 2014;Okur & Özsoy, 2013;Tanrıkulu & Yogurtcu, 2018;VanTassel-Baska, 2003). In addition, there are studies examining the views and attitudes of students, teachers and parents of students about SACs and the education given in these centers ( Epcacan & Ural, 2019;Koc, 2016;Saglam & Polat, 2020;Weiner, 1992).…”
Section: Motivation Of Gifted To Academic Coursesmentioning
confidence: 99%
“…In the literature, it is observed that metaphor studies conducted with gifted secondary school students are aimed at evaluating education, school, science, and art center, different branch courses and concepts (Turkish, music, mathematics, social studies), and teacher perception (Oğuz, 2020;Oğurlu, Öpengin, et al Fast, 2015;Öztürk, Akkan, & Kaplan, 2014;Aslan &Doğan, Şahin, A., Sümer, M., Tarsuslu, B., Tuncay, S. (2023), Gifted andTypically Developing Students' Perceptions of the Covid-19 Outbreak, Sabuncuoglu Serefeddin Health Sciences, 5(1), 1-21 2016;Bolat, 2020;Akça, Şen & Kurtaslan, 2019;Su, Sağlam & Mutlu, 2017;Çelik Şahin, 2014).…”
Section: öZetmentioning
confidence: 99%
“…Öğrencilerin bilime algılarını ölçmeye yönelik yapılan araştırmalarda (Doğan, Koyuncu ve Doğan, 2020;Bahadır, 2020;Akarca, Çobanoğlu ve Karataş, 2020;Terzi, Vatandaş ve Algıtaşı, 2020;Bolat, 2020;Kaygısız, 2020;Şenel ve Aslan, 2014;Özgün, Gürkan ve Kahraman, 2018;Kalaycı, 2018;Aktamış ve Dönmez, 2016;Aslan ve Doğan, 2016;Özsoy, 2014, Şükrü, Sağlam ve Mutlu, 2017Dönmez, 2017;Bıyıklı, Başbay ve Başbay, 2014;Nacaroğlu ve Mutlu, 2020;Bartan, 2019;Arık ve Özdemir, 2016;Berber ve Güzel, 2009;Ekici, 2016;Gürkan, Özgün ve Kahraman 2018) öğrencilerin bilimin gerçeklerin ispatı yönüne ve doğa bilimlerine odaklandıkları görülmektedir. Fetah, Çelik ve Aktürk (2014) ortaokul öğrencilerinin Facebook'a yönelik algılarını belirlemek için yaptıkları çalışmada Facebook için genelde olumlu tutumlar sergilediklerini tespit etmişlerdir.…”
Section: Literatür İncelemesiunclassified